Resumé of the challenges and burden of living with transplanted hearts for >31 years - Javier Delmo, Eva Maria (Cardiovasc Diagn Ther, 2021)
Heart transplantation has extended the lives of many patients with end-stage heart failure. Although beset with the arduous aftermaths of immunosuppression, those who survived live meaningful lives similar to that of the general population. In this series, heart transplantation has led to a considerable extension of life span of >31–34 years. Development of cardiac allograft vasculopathy is a major concern in the long-term follow-up of transplant patients. Immunosuppressive drugs have a major impact on the development and progression of cardiac allograft vasculopathy and the main cause of cardiac allograft loss after the first post-transplantation year. Post-transplant neoplasia remains a challenging long-term problem for patients after orthotopic heart transplantation. Post-transplant lymphoproliferative disease appears to be largely the result of the effectiveness of current agents used for long-term immunosuppression, and the neoplasms typically harbor the Epstein Barr virus genome, which is presumed to play a major role in neoplastic transformation. Post-transplantation, new diseases may occur or there may be worsening of pre-existing diseases. By the end of the 5(th) year, all suffered from hypertension. Renal insufficiency developed within 5 years after transplantation, and 10% have a creatinine value of >2.5 mg/dL. Hyperlipidemia, mostly hypercholesterolemia occurs especially in patients on tacrolimus or everolimus. Quality of life is not impaired despite somatic problems. In this period >31 years post-post-orthotopic heart transplantation, they even reported a surprising increase in their emotional well-being. The 10 patients are active and satisfied with their daily lives. They regard their own life as meaningful, have good families and active social relations. Nonetheless, it is burdened by chronic allograft vasculopathy and immunosuppression sequelae, the main limiting factors for survival, which needed to be constantly addressed throughout their lifetime. This brief report provides an insight into the challenges and burden patients living >31 years with transplanted hearts are confronted with.